Effects of letrozole on hippocampal and cortical catecholaminergic neurotransmitter levels, neural cell adhesion molecule expression and spatial learning and memory in female rats - Aydin, M.; Yilmaz, B.; Alcin, E.; Nedzvetsky, V. S.; Sahin, Z.; Tuzcu, M. (Pergamon-Elsevier Science Ltd, 2008)
We have investigated effects of letrozole, an aromatase inhibitor, on spatial learning and memory, expression of neural cell adhesion molecules (NCAM) and catecholaminergic neurotransmitters in the hippocampus and cortex of female rats. In the intact model, adult Sprague-Dawley rats were divided into four groups (n=8). Control received saline alone. Letrozole was administered to the animals in the second and third groups by daily oral gavage at 0.2 and 1 mg/kg doses, respectively, for 6 weeks. Another group of letrozole-treated rats was allowed to recover for 2 weeks. In the second model, 24 rats were ovariectomized (ovx) and the first group served as control. The second group received letrozole (1 mg/kg) for 6 weeks. Ovx rats in the third group were given letrozole (1 mu g/kg) plus estradiol (E-2) (10 mu g/rat). At the end, all rats were tested in a spatial version of the Morris water maze. Then they were decapitated and the brains rapidly removed. Catecholamine concentrations were determined by high performance liquid chromatography with electrochemical detection. NCAM 180,140 and 120 isoforms were detected by Western blotting. Uterine weights were significantly reduced by letrozole in a dose-dependent manner (P<0.01) which returned to control values following 2 weeks of recovery (P<0.05). Serum E-2 levels followed a similar course (P<0.01). Although improvement in spatial learning performance of letrozole-treated rats was not statistically significant, the high-dose letrozole-treated group remained significantly longer in the target quadrant compared with the control (P<0.05). Administration of letrozole to ovx animals significantly reduced the latency (P<0.001) and increased the probe trial performance compared with ovx controls (P<0.05). Letrozole increased expression of NCAM 180 and NCAM 140 in both hippocampus and cortex of intact rats. In the cortex samples of ovx animals, NCAM 180 was overall lower than the intact control values (P<0.05). Noradrenaline, dopamine and their metabolites were decreased in the hippocampus of the letrozole-treated group (P<0.01). Letrozole had differential effects on noradrenaline and dopamine content in the cortex. It appears that inhibition of estrogen synthesis in the brain may have beneficial effects on spatial memory. We suggest that structural changes such as NCAM expression and catecholaminergic neurotransmitters in the hippocampus and prefrontal cortex may be the neural basis for estrogen-dependent alterations in cognitive functions. (C) 2008 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: aromatase inhibitor; estrogen; NCAM; noradrenaline; Morris water maze; cognition